Properties of Functions with Symmetric Points Involving Subordination. (11th January 2022) - Raza, Malik Ali; Bukhari, Syed Zakar Hussain; Ahmed, Imtiaz; Ashfaq, Muhammad; Nazir, Maryam
Abstract : We study a new subclass of functions with symmetric points and derive an equivalent formulation of these functions in term of subordination. Moreover, we find coefficient estimates and discuss characterizations for functions belonging to this new class. We also obtain distortion and growth results. We relate our results with the existing literature of the subject.